2021
DOI: 10.1029/2021ja029192
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mid‐latitude Density Irregularities and Scintillation in North America During the 7–8 September 2017 Storm

Abstract: While high-latitude and equatorial density irregularities and scintillations have been explored in detail, studies on mid-latitude (30°-60° magnetic latitude (MLAT)) density irregularities and scintillation are scarce, and their properties are far less understood. Statistically, radio signal scintillations are indeed much more common in the equatorial and high-latitude ionosphere, whereas those are rare in the mid-latitude ionosphere (Basu et al., 2002;Prikryl et al., 2015). Global surveys of satellite-based G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Because the growth rate of the gradient drift instability is positive under these conditions, the northeast side boundary of the SED provides a favorable condition for the growth of perturbations. The development of irregularities and scintillations at the poleward boundary of the SED was also identified during the 8 September 2017 storm, and the formation of the turbulences at the boundary was explained in terms of the gradient drift instability (Nishimura et al., 2021). These studies along with our observations indicate that plasma depletions can develop in midlatitudes by local plasma instabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the growth rate of the gradient drift instability is positive under these conditions, the northeast side boundary of the SED provides a favorable condition for the growth of perturbations. The development of irregularities and scintillations at the poleward boundary of the SED was also identified during the 8 September 2017 storm, and the formation of the turbulences at the boundary was explained in terms of the gradient drift instability (Nishimura et al., 2021). These studies along with our observations indicate that plasma depletions can develop in midlatitudes by local plasma instabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is largely based on the morphology of midlatitude depletions and the simultaneous detection of EPBs at the same magnetic meridian. However, midlatitude depletions are also explained in association with other sources such as traveling ionospheric disturbances (TIDs) (Kil et al., 2016; Nishioka et al., 2009), poleward streaming of plasma depletions (Zakharenkova & Cherniak, 2020), or plasma density gradient formed by storm enhanced density (SED) (Nishimura et al., 2021; Sun et al., 2013). From the total electron content (TEC) maps over Japan, Nishioka et al.…”
Section: Introductionmentioning
confidence: 99%
“…GPS receivers have been used to show that density irregularities are present in the plume (Heine et al., 2017; Mrak et al., 2020). The plume can evolve to multiple channels and density irregularities are localized to their steep TEC gradients (Nishimura et al., 2021). Super Dual Auroral Radar Network (SuperDARN) echoes are also enhanced at the TEC gradients, indicating that density irregularities extend down to 10s of meter wavelengths (Nishimura et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The plume can evolve to multiple channels and density irregularities are localized to their steep TEC gradients (Nishimura et al., 2021). Super Dual Auroral Radar Network (SuperDARN) echoes are also enhanced at the TEC gradients, indicating that density irregularities extend down to 10s of meter wavelengths (Nishimura et al., 2021). Velocity observations in the ionosphere have shown that SAPS also contain fine‐scale (∼tens of km) structures that propagate quasi‐periodically (Erickson et al., 2002; Foster et al., 2004; Makarevich & Bristow, 2014; Oksavik et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the eastern Asian sector, unique severe EPIs events occurred as depleted plasma density structures that extend northeastward from low latitudes to mid-latitudes on 8 September 2017 were confirmed in the Swarm in-situ Ne measurements as reported by Aa et al (2018). In addition, in the American sector, the midlatitude irregularities that resided near the Storm Enhanced Density (SED) base and ionosphere main trough were also reported to be generated via the gradient drift instability (Nishimura et al, 2021); however, this kind of plasma irregularities are mainly located close to the subaurora region, and they are not the same as the low-latitude EPIs as addressed in our study. Even though, the mechanism of such subauroral plasma irregularities during a storm and the question whether these irregularities are related to the expansion of EPIs from low latitudes are still of interest, which require further study.…”
Section: In-situ Observations Of Small-scale Plasma Irregularities From Swarm Satellitesmentioning
confidence: 69%